Agile Based Development of a Web Ticketing Platform Using Scrum: A Case Study of the A5 Ticket System - Yenni Fatman; Mukhlis Aburizal Khordowi; Ikbal Hidayat Pratama (Deparment Information System, Siliwangi University, 2026)
This study presents an agile based development of a web ticketing platform A5 Ticket using the Scrum framework, examined through a case study approach. The primary motivation is to address the growing need for an efficient, scalable, and user centric online ticket management system in the digital era, capable of serving end users, event organizers, and system administrators within a single integrated platform. The Scrum framework was adopted as the development methodology for its iterative and collaborative nature, which engages stakeholders at every stage of the development cycle. The system was developed through six Scrum stages: Product Backlog, Sprint Planning, Sprint Execution, Daily Stand-Up, Sprint Review, and Sprint Retrospective. Key features of the developed platform include user registration and login, ticket search and ordering, event management for organizers, sales reporting for administrators, and payment gateway integration. The platform is accessible on both desktop and mobile devices, featuring an intuitive, responsive user interface. The research findings highlight the effectiveness of the Scrum methodology in ensuring platform responsiveness, data security, and ease of use. User satisfaction was evaluated using a Likert scale survey distributed to users, organizers, and administrators, while qualitative insights were gathered through semi structured interviews. The results demonstrate that agile driven iterative development through Scrum effectively addressed user requirements at each sprint cycle, leading to a functional, secure, and user friendly event ticketing platform. This case study contributes practical evidence on the application of Scrum in web-based ticketing system development and serves as a reference for future agile software engineering projects in similar domains